ANALYSIS OF TOURIST VILLAGE AND TOURIST CHARACTER IN KAMPOENG LAMA VILLAGE DELI SERDANG REGENCY - Nasution, Rahmi Khairani; Harahap, R. Hamdani; Kurniawati, Dewi; Ridho, Hatta (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2024)
The aim of this research is to analyze the potential of tourist villages and the characteristics of tourists in the Kampung Lama village of Deli Serdang district. This type of research is mixed method. Data analysis are carried out with stages of data reduction, data presentation and conclusion and then the data is analyzed qualitatively. The results of this study suggest that The Kampoeng Lama Tourist Village has tremendous potential, although it does not have a special tourist attraction but it can exploit the potential to become a tourist village. As for the characteristics of the tourists who visited it is seen from the demographic socio 18-24 years of age as 70 people (68%), more visitors male type 53 (51,5%), with a diploma education of 49 people (47.6%), unmarried status 73 people (70,9%).